Politics and the nation Britain in the mid-eighteenth century - Harris, Bob, 1964- (Oxford University Press, 2002)
In this study of British politics and political culture in the 18th-century the author reconstructs a political world in which vital issues continued to exercise the minds and emotions of the contemporary political nation.